IT/QA and Regulatory Aspects of Digital Pathology: Results of the 8th ESTP International Workshop. (August 2022) - Boisclair, Julie; Bawa, Bhupinder; Barale-Thomas, Erio; Bertrand, Lise; Carter, Jonathan; Crossland, Richard; Dorn, Celine; Forest, Thomas; Grote, Sabine; Gilis, Anja; Hildebrand, Deon; Knight, Brian; et al.
Digital toxicologic histopathology has been broadly adopted in preclinical compound development for informal consultation and peer review. There is now increased interest in implementing the technology for good laboratory practice–regulated study evaluations. However, the implementation is not straightforward because systems and work processes require qualification and validation, with consideration also given to security. As a result of the high-throughput, high-volume nature of safety evaluations, computer performance, ergonomics, efficiency, and integration with laboratory information management systems are further key considerations. The European Society of Toxicologic Pathology organized an international expert workshop with participation by toxicologic pathologists, quality assurance/regulatory experts, and information technology experts to discuss qualification and validation of digital histopathology systems in a good laboratory practice environment, and to share the resulting conclusions broadly in the toxicologic pathology community.